Struttura e costruzione / Structure and Construction Nuova edizione / New Edition - GULLI, RICCARDO (Manuali - Scienze Tecnologiche, 2012)
This book explores several aspects of the variegated relationship that connects the operational principles of a structure to its translation into written form, between the laws that govern its structural rationale and the technical solutions that decree the feasibility of its construction. This is considered an essential subject for the training of aspiring engineers, whose education is often strongly conditioned by a didactic approach that divides the knowledge of construction into circumscribed and independent disciplinary units. This same approach negatively connotes the progressive transformation of the professional profile of the contemporary engineer, from the original figure of a designer of technical solutions to that of a specialist-assessor of structural performance. The result is that such figures sometimes lack the critical instruments inherent to a knowledge that does not begin and end within models of scientific explanation, but has to be comprised within a broader cultural dimension featuring the coexistence and mutual nourishment of different branches of knowledge, including History, Science and Design through to the ultimate dynamics of Architecture.